Effect of gender on pain perception and analgesic consumption in laparoscopic cholecystectomy: An observational study - Aziza M Hussain; Fauzia A Khan; Aliya Ahmed; Tabish Chawla; Syed I Azam (Wolters Kluwer Medknow Publications, 2013)
Background: Evidence regarding gender affecting the response to pain and its treatment is inconsistent in literature. The objective of this prospective, observational study was to determine the effect of gender on pain perception and postoperative analgesic consumption in patients undergoing laparoscopic cholecystectomy. Materials and Methods: We recruited 60 male and 60 female patients undergoing elective laparoscopic cholecystectomy. Patients were observed for additional intraoperative and postoperative analgesia. Numerical rating scale was documented at 10 min interval for 1 h in post-anesthesia recovery room and at 4, 8, and 12 h postoperatively. Boluses of tramadol given as rescue analgesia were also noted. There were no dropouts. Results: The mean pain scores were significantly higher in female patients at 20 and 30 min following surgery. Mean dose of tramadol consumption was significantly higher in female patients for the first postoperative hour (P = 0.002), but not in the later period. Conclusion: Female patients exhibited greater intensity of pain and required higher doses of analgesics compared to males in in the immediate postoperative period in order to achieve a similar degree of analgesia.